1996
DOI: 10.1111/j.1365-2621.1996.tb14719.x
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Structure of Fat Globule Surface Layers in Recombined Milk

Abstract: Protein coverage, composition and structure of surface layers of fat globules in recombined milk were determined. Average protein load was ϳ6 mg/m 2 fat surface. Both casein and whey proteins were present in the fat globule surface layer, with casein adsorbed in preference to whey proteins and ␣ s (␣ s1 ϩ␣ s2 )-casein adsorbed in preference to ␤-casein. Transmission electron microscopy showed that the surface layer of fat globule was made up of casein micelles, fragments of casein micelles and a thin layer of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 16 publications
2
27
0
Order By: Relevance
“…4), signs of clustering were observed only when skim milk was incubated with TGase for 24 h and the recombined milk was homogenised at 800 bar. Sharma, Singh, and Taylor (1996) reported that spreading of casein micelles is more pronounced in recombined milk than in raw whole milk, leading to a lower protein surface load in the former. Hence, at similar protein and fat contents, a more extensive formation of clusters would be expected in raw whole milk than in recombined milk which may explain the results found here.…”
Section: Discussionmentioning
confidence: 97%
“…4), signs of clustering were observed only when skim milk was incubated with TGase for 24 h and the recombined milk was homogenised at 800 bar. Sharma, Singh, and Taylor (1996) reported that spreading of casein micelles is more pronounced in recombined milk than in raw whole milk, leading to a lower protein surface load in the former. Hence, at similar protein and fat contents, a more extensive formation of clusters would be expected in raw whole milk than in recombined milk which may explain the results found here.…”
Section: Discussionmentioning
confidence: 97%
“…Their results are in agreement with studies performed with heat treated and homogenised milks. Considering the organisation of proteins, it has been shown that the milk fat globule surfaces were covered with (i) intact casein micelles, (ii) partially spread casein micelles, (iii) smaller particles, which probably result from the desintegration of casein micelles and (iv) a thin layer of proteins, which was probably whey proteins [27,28]. The sequence of homogenisation and heating changes the structure and the composition of the synthetic FGM [25].…”
Section: Discussionmentioning
confidence: 99%
“…Britten et al (2008) showed that the total protein content of buttermilk (including caseins, whey proteins, and MFGM proteins) was reduced from 24.5 g L À1 to 5.2 g L À1 after one washing step with 10 times the starting volume of UF Saline solution (0.9% NaCl) Cavaletto et al, 1999;Cebo et al, 2010;Fortunato et al, 2003;Keenan et al, 1971;Patton, 1982 Phosphate Cavaletto et al, 1999;Cebo et al, 2010;Dickow et al, 2011;Horisberger et al, 1977;Kathriarachchi et al, 2014;Liao et al, 2011;Mather & Keenan, 1975;Nejjar et al, 1986;Ong et al, 2010;Patton, 1982;Patton & Huston, 1986;Sharma et al, 1996;Ye et al, 2002;Zamora et al, 2012;Zheng et al, 201330e45 C Jenness & Palmer, 1945Montagne et al, 1999;Oehlmann et al, 1994;Shimizu & Yamauchi, 1982;Wiese & Palmer, 1932 1000e3000 (low) Cavaletto et al, 1999;Cebo, Caillat, Bouvier, & Martin, 2010;Chien & Richardson, 1967;Dalgleish & Banks, 1991;Dickow, Larsen, Hammershøj, & Wiking, 2011;Fortunato et al, 2003;Horisberger et al, 1977;Iametti et al, 1997;Kathriarachchi et al, 2014;…”
Section: The Impact Of Washing On Fat Globules and The Mfgmmentioning
confidence: 97%
“…Overview of various washing conditions using lab-scale centrifuges Kim & Nawar, 1992;Liao, Alvarado, Phinney, & L€ onnerdal, 2011;Montagne et al, 1999;Nejjar et al, 1986;Patton, 1982;Reinhardt & Lippolis, 2006;Sharma et al, 1996;Shimizu & Yamauchi, 1982;Vanderghem et al, 2008;Zheng et al, 2013. …”
mentioning
confidence: 99%